Representasi Peran Gender dalam Film Baby Blues - Jannah, Debby Vironica Nur; Kusuma, Ade (Az-Zahra: Journal of Gender and Family Studies, 2023)
Abstract: From the reformation period until now, Indonesian cinema has been trying to raise issues about gender equality or inequality. Gender stereotypes from the patriarchal culture that are inherent in some Indonesian people often bring gender inequalities. One of them is in the context of the division of gender roles in the family. It will not be a problem if the division does not cause gender inequalities. However, in reality there is the pressure that burdens one party. This study aims to reveal how the representation of gender roles in the film Baby Blues uses John Fiske's semiotic analysis method, which consists of three levels of analysis, reality, representation, and ideology. The study shows that gender stereotype is incorporated in both traditional and contemporary viewpoint of gender roles.. In the traditional role, men play a role in the public sector and women play a role in the domestic sector. While the new perspective tries to break it down by showing men who are starting to be domesticated from the results of the exchange of roles that happened before.